“PASANTIAN”IN BALI AND ITS RENAISSANCE IN GLOBALIZATION ERA - Sudirga, I Komang (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2013)
Pasantian, which means reading and reciting a literary work, is growing, developing and resurrecting resistively in the life of the Balinese community in the globalization era. This study tries to answer the following questions: (1) what was the renaissance of pasantian in the globalization era in Bali like; (2) what factors contributed to the renaissance of pasantian in the globalization era in Bali; (3) what was the meaning of the renaissance of pasantian in the globalization era in Bali? This study in which qualitative method was used. It was intended to identify the existence of pasantian and its dynamism through its renaissance in the globalization era. The theory of deconstruction (Derrida, in Norris, 2008), the theory of practice (Bourdieu in Takwin, 2009 and Fashri, 2007), the theory of postmodern (Piliang, 2004, and Piliang, 2004a), and the theory of hegemony (Gramsci, in Barker, 2005) were eclectically used to analyze the data. The result showed that the renaissance of pasantian took place in three periods; the initial renaissance took place from 1979 to 1990, the second from 1991 to 1998, and the third from 1999 to 2010s. Such a renaissance was supported by cultural factors. In addition, political and economic factors also contributed to the renaissance of pasantian. It had socio-cultural, and economic effects, which led to multi-meanings such as educational meaning, entertainment meaning, the meaning of politics of image, the meaning of hypermorality, and the meaning of maintenance of socio-cultural meanings.